In situ atomic-scale observation of AuCu alloy nanowire with superplasticity and high strength at room temperature. (August 2021) - Fu, L.; Yang, C.; Wei, R.; Pei, X.; Teng, J.; Kong, D.; Lu, Y.; Guo, Y.; Liu, T.; Hu, Y.; Yin, B.; Zhang, Z.; et al.
Abstract: Metallic nanowires usually exhibit ultrahigh strength but suffered low ductility. Previous studies on pure metals suggested this strength-ductility trade-off results from limiting the dislocation activities. However, it is unclear whether such deformation model is valid for a solid solution alloy as well. Here, for the first time, the atomic-scale deformation process of AuCu nanowires with size of ∼16 nm was investigated in situ. The results show the NWs exhibit superplasticity (∼185%) and high strengths (∼2.98 GPa) at room temperature. It was discovered that superplasticity originates from continuous full dislocation nucleation and disappearance, as well as dislocation dipole formation and annihilation etc., which differ from the previous studies in pure metals. The observed full dislocation activities, also different from the ones in the previous studies, suggested that, as the size of the metals is below ∼100 nm, their deformation should be governed by partial dislocation and twinning. Graphical abstract: Image 1